Manajemen Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kompetensi Kepribadian Guru Taman Kanak-Kanak - Maemunah, Nuroni; Sauri, Sopyan; Hanafiah, Nanang (Edukasi: Journal of Educational Research, 2021)
This research is motivated by the importance of the principal's academic supervision management in improving the personality competence of kindergarten teachers. This research was compiled on the basis of the word of Allah SWT in the Qur'an Surah Al-Baqarah verses 31-32, philosophical idealism and Terry's theory of management. The purpose of this study was to determine the management of the principal's academic supervision in improving the personality competence of kindergarten teachers. The principal's academic supervision management includes planning, implementation, supervision and evaluation. This study uses a descriptive qualitative approach. The data collection method used is the method of interview, observation and documentation with the principal and teachers as informants. Data collection is intended to answer research problems. Based on the research, it was found: (a) The planning of the principal's academic supervision includes the preparation of a supervision program and the manufacture of supervision instruments, (b) The implementation of supervision uses a directive approach, traditional models, individual and group techniques. (c) Supervision and evaluation of supervision includes monitoring, preparation of follow-up plans and reporting, (d) Supporting factors for supervision are the presence of adequate resources, while the inhibiting factors for supervision include limited understanding of the importance of the management of academic supervision of principals. Based on the results of the study, it was concluded that: (a) The planning function has not been fully implemented, (b) The implementation of supervision is in accordance with the theory of implementation of supervision, (c) Supervision supervision does not carry out evaluations, and (d) Supporting factors for academic supervision are the presence of high resources. academic supervision is a limited understanding of the importance of academic supervision management. While the implications of this research are: (a) Planning for comprehensive academic supervision will have an impact on weak implementation and supervision, waste of resources and weak institutional accountability, (b) Implementation of supervision using appropriate approaches, models and techniques will affect the success of supervision implementation, (c) Supervision and evaluation have not been fully implemented, so that the success of the program can be measured accurately, d) Supporting and inhibiting factors of academic supervision if analyzed properly, can facilitate the principal in making decisions.